(untitled) (Ameghiniana, 2014)
Recent fieldtrips led to the discovery of new specimens of a recently described interatheriid from Northwestern Argentina, Antofagastia turneri. These new specimens show some intraspecific variation regarding size and certain coronal features. Additionally, two fossil remains bearing lower teeth, one of them previously referred as Punapithecus minor, were analyzed. Overall size and some occlusal traits indicate that this material may be considered as closer to Antofagastia than to Punapithecus. The new specimens bring new information regarding intraspecific and ontogenetic variation, which represents a valuable tool to assess diagnostic features present in fossil fragments and isolated dental pieces.